C1q/TNF-Related Protein 9 Attenuates Atherosclerosis by Inhibiting Hyperglycemia-Induced Endothelial Cell Senescence Through the AMPKα/KLF4 Signaling Pathway - Wang, Gang; Han, Baihe; Zhang, Ruoxi; Liu, Qi; Wang, Xuedong; Huang, Xingtao; Liu, Dandan; Qiao, Weishen; Yang, Mengyue; Luo, Xing; Hou, Jingbo; Yu, Bo (Frontiers in Pharmacology, 2021)
Hyperglycemia-induced endothelial cell senescence has been widely reported to be involved in the pathogenesis of type 2 diabetes mellitus (T2DM)‒associated atherosclerosis. Endothelial senescence inhibition is valuable for attenuating atherosclerosis progression. C1q/tumor necrosis factor-related protein 9 (CTRP9), an emerging potential cardiokine, exerts a significant protective effect with respect to atherosclerosis, particularly in endothelial cells. However, the exact mechanism by which CTRP9 prevents endothelial cells from hyperglycemia-induced senescence remains unclear. This study aimed to investigate the effects of CTRP9 on hyperglycemia-induced endothelial cell senescence and atherosclerotic plaque formation in diabetic ApoE−/− mice. Human umbilical vein endothelial cells (HUVECs) were cultured in normal glucose (NG; 5.5 mM) and high glucose (HG; 40 mM) with or without recombinant human CTRP9 protein (3 μg/ml) for 48 h. Purified lentiviruses overexpressing CTRP9 (Lv-CTRP9) and control vectors containing green fluorescent protein (Lv-GFP) were injected via the tail vein into streptozotocin-induced diabetic ApoE−/− mice. Results revealed that exposure of HUVECs to HG significantly increased the expression of Krüppel-like factor 4 (KLF4) and cyclin-dependent kinase inhibitor p21 (p21) and decreased that of telomerase reverse transcriptase (TERT). Treatment with recombinant human CTRP9 protein protected HUVECs from HG-induced premature senescence and dysfunction. CTRP9 promoted the phosphorylation of AMP-activated kinase (AMPK), attenuated the expression of KLF4 and p21 induced by HG, and increased the expression of TERT in HUVECs. Furthermore, in the background of AMPKα knockdown or KLF4 activation, the protective effects of CTRP9 were abolished. In-vivo experiments showed that overexpression of CTRP9 inhibited vascular senescence and reduced atherosclerotic plaque formation in ApoE−/− mice with diabetes. In conclusion, we demonstrate that KLF4 upregulation plays a crucial role in HG-induced endothelial senescence. This anti-atherosclerotic effect of CTRP9 may be partly attributed to inhibit HG-induced endothelial senescence through the AMPKα/KLF4-dependent mechanism, suggesting that CTRP9 could benefit further therapeutic approaches for T2DM-associated atherosclerosis.